Differential equations with boundary-value problems - Zill, Dennis G., 1940- (Cengage Learning, 2018)
"Differential equations with boundary-value problems, 8E, International Metric Edition strikes a balance between the analytical, qualitative, and quantitative approaches to the study of differential equations. Beginning engineering and math students like you benefit from this accessible text's wealth of pedagogical aids, including an abundance of examples, explanations, "Remarks" boxes, definitions, and group projects. Written in a straightforward, readable, and helpful style, the book provides you with a thorough treatment of boundary-value problems and partial differential equations"--Publisher website.